THE CRITICAL STANCE TOWARDS MOSCHOPOLITAN PUBLICATIONS ABOUT SAINTS OF THESSALY AND CORYDALEUS’ EPISTOLOGRAPHY AND RHETORIC DURING THE EIGHTEENTH CENTURY - Tempelis, Elias (Analecta Stagorum et Meteororum, 2022)
This study attempts to explain the reasons why three publications from the Moschopolis printing press—on the saints of Thessaly, Seraphim and Bessarion, and on the correspondence and rhetoric of the lark—were criticized and republished in the 18th century by European printing houses (Venice, Bucharest, and Halle). This analysis is based on the available data concerning the ideology and activities of the individuals involved in each publishing endeavor, as well as the relationships between them.